Shadow education, pandemic style: Social class, race, and supplemental education during Covid-19. (February 2023) - Lee, Jennifer C.; Quadlin, Natasha; Ambriz, Denise
Abstract: Research on shadow education—i.e., one-on-one or group learning intended to supplement children's experiences in school—has documented persistent social class and racial/ethnic inequalities. Yet, as with many things during the Covid-19 pandemic, the nature of shadow education changed dramatically. Much supplemental education shifted online, potentially increasing accessibility; many universities became testoptional, potentially reducing the demand for the shadow education industry; and a new form of shadow education—learning pods—emerged to take pandemic schooling from a more individual to a more collective experience. In this article, we use data from a sample of U.S. parents of K-12 students stratified by race/ethnicity (N = 1911) to assess social class and racial/ethnic inequalities in shadow education in 2020–21, the first full academic year of the Covid-19 pandemic. We are also the first scholars, to our knowledge, to assess high-quality data on the use of learning pods. We find that during the pandemic, African American and South Asian students were more likely than White student to use test preparation services and online supplemental education, and that African Americans, East Asians and Latinx were more likely to utilize private tutoring. We find few disparities by family income, however, thus supporting the idea that some forms of shadow education have become more accessible than they once were. Regarding learning pods, we find that pods were most common among African American families and families with parents who were less educated and worked fulltime. Thus, most learning pods were not a means of "opportunity hoarding, " as some scholars originally feared, but instead provided sorely needed childcare and support during a time of social turbulence.